JĘZYKOWO-KULTUROWE KONSEKWENCJE KONTAKTU MAJÓW Z HISZPANAMI - Tuszyńska, Boguchwała; Jagodziński, Kajetan (Scripta Neophilologica Posnaniensia, 2019)
In the paper, an attempt has been made to describe the cultural and linguistic contacts between the local Maya civilization and the Spanish conquistadores. The consequences of that contact for the local culture and Mayan-Spanish interrelationships have been discussed. The authors emphasize that as a result of this intensive and long-time contact, the Spanish culture has not been completely imposed on the Maya culture, nor has Spanish language completely subjugated the Mayan language.